Returns to Birthweight - Behrman, Jere R.; Rosenzweig, Mark R. (The Review of Economics and Statistics, 2004)
We use data on monozygotic twins to obtain improved estimates of the effect of intrauterine nutrient intake on adult health and earnings and thus to evaluate the efficacy of programs aimed at increasing birthweight. We use the results to evaluate the bias in cross-sectional estimates and to assess the proposition that health conditions play a major role in determining the world distribution of income. We show that there is considerable variation in the incidence of low birthweight across countries, and our estimates suggest that there are real payoffs to increasing body weight at birth. Increasing birthweight increases adult schooling attainment and adult height for babies at most levels of birthweight, but has no effect on adult body mass. The effect of increasing birthweight on schooling, moreover, is underestimated by 50x% if there is no control for genetic and family background endowments as in cross-sectional estimates. We also find evidence that augmenting birthweight among lower-birthweight babies, but not among higher-birthweight babies, has significant labor market payoffs. However, shifting the distribution of birthweights in developing countries to that in the United States would reduce world earnings inequality by less than 1%, far less than indicated by the cross-country correlation between per-worker GDP and birthweight.